Broad assessment of bioactivity of a collection of spiroindane pyrrolidines through "cell painting". Issue 13 (1st July 2020) - Singh, Manvendra; Garza, Nathan; Pearson, Zachary; Douglas, Justin; Boskovic, Zarko
Graphical abstract: Abstract: A collection of small molecules has been synthesized by composing photo-cycloaddition, C–H functionalization, and N -capping strategies. Multidimensional biological fingerprints of molecules comprising this collection have been recorded as changes in cell and organelle morphology. This untargeted, phenotypic approach allowed for a broad assessment of biological activity to be determined. Reproducibility and the magnitude of measured fingerprints revealed activity of several treatments. Reactive functional groups, such as imines, dominated the observed activity. Two non-reactive candidate compounds with distinct bioactivity fingerprints were identified, as well.